The best book of ponies - Budd, Jackie (New York : Kingfisher, 1999)
Introduces pony-keeping, explaining breeding, grooming, riding clothes and equipment, and riding lessons. Includes a glossary.
Includes index.
Keywords: Ponies -- Juvenile literature; Horsemanship -- Juvenile literature; Ponies; Horsemanship